Exogenous Cardiac Bridging Integrator 1 Benefits Mouse Hearts With Pre-existing Pressure Overload-Induced Heart Failure - Li, Jing; Agvanian, Sosse; Zhou, Kang; Shaw, Robin M.; Hong, TingTing (Frontiers in Physiology, 2020)
Background: Cardiac bridging integrator 1 (cBIN1) organizes transverse tubule (t-tubule) membrane calcium handling microdomains required for normal beat-to-beat contractility. cBIN1 is transcriptionally reduced in heart failure (HF). We recently found that cBIN1 pretreatment can limit HF development in stressed mice. Here we aim to explore whether cBIN1 replacement therapy can improve myocardial function in continuously stressed hearts with pre-existing HF. Methods: Adult male mice were subjected to sham or transverse aortic constriction (TAC) surgery at the age of 8-10 weeks old. Adeno-associated virus 9 (AAV9) transducing cBIN1-V5 or GFP-V5 (3x1010 vg) was administered through retro-orbital injection at 5 weeks post-TAC. Mice were followed by echocardiography until 20 weeks after TAC. Overall survival, heart and lung weight, and HF incidence were determined. In a second set of animals in which AAV9-cBIN1 pretreatment prevents HF, we recorded cardiac pressure-volume (PV) loops and obtained myocardial immunofluorescence imaging. Results: The overall Kaplan-Meir survival of AAV9-cBIN1 mice was 77.8%, indicating a significant partial rescue between AAV9-GFP (58.8%) and Sham (100%) treated mice. In mice with ejection fraction ≥30% prior to AAV9 injection at 5 weeks post-TAC, AAV9-cBIN1 significantly increased survival to 93.3%, compared to 62.5% survival for AAV9-GFP treated mice. The effect of exogenous cBIN1 was to attenuate TAC-induced left ventricular dilation and prevent further HF development. Recovery of ejection fraction (EF) also occurs in AAV9-cBIN1-treated mice. We found that EF increases to a peak at 6-8 weeks post-viral injection. Furthermore, PV loop analysis identified that AAV9-cBIN1 increases both systolic and diastolic function of the post-TAC hearts. At the myocyte level, AAV9-cBIN1 normalizes cBIN1 expression, t-tubule membrane intensity, and intracellular distribution of Cav1.2 and ryanodine receptors. Conclusions: In mice with pre-existing HF, exogenous cBIN1 can normalize t-tubule calcium handling microdomains, limit HF progression, rescue cardiac function, and improve survival.